Latency and interval therapy affect the evolution in metastatic colorectal cancer - Nikbakht, Hamid; Jessa, Selin; Sukhai, Mahadeo A.; Arseneault, Madeleine; Zhang, Tong; Letourneau, Louis; Thomas, Mariam; Bourgey, Mathieu; Roehrl, Michael H. A.; Eveleigh, Robert; Chen, Eric X.; Krzyzanowska, Monika; et al. (Scientific reports, 2020)
While comparison of primary tumor and metastases has highlighted genomic heterogeneity in colorectal cancer (CRC), previous studies have focused on a single metastatic site or limited genomic testing. Combining data from whole exome and ultra-deep targeted sequencing, we explored possible evolutionary trajectories beyond the status of these mutations, particularly among patient-matched metastatic tumors. Our findings confirm the persistence of known clinically-relevant mutations (e.g., those of RAS family of oncogenes) in CRC primary and metastases, yet reveal that latency and interval systemic therapy affect the course of evolutionary events within metastatic lesions. Specifically, our analysis of patient-matched primary and multiple metastatic lesions, developed over time, showed a similar genetic composition for liver metastatic tumors, which were 21-months apart. This genetic makeup was different from those identified in lung metastases developed before manifestation of the second liver metastasis. These results underscore the role of latency in the evolutionary path of metastatic CRC and may have implications for future treatment options.